The influence of outdoor and environmental educational program toward enhancing leadership skill among physical and health education students / Nur Intan Hazirah Hamidun - Hamidun, Nur Intan Hazirah (Faculty of Education, 2014)
Outdoor education could be connected with practices that could enrich experience and positive attitudes towards developing healthy individuals, mentally, physically and spiritualy in individuals. This study strives to indentify the perception of Physical and Health Education students in the Faculty of Education; UiTM pertaining of how outdoor education brings positive effect in terms of enhancing leadership skill among students. The samples, consisting of 60 respondents were selected from the Faculty of Education, UiTM Shah Alam. The selection of the respondent was done using random sampling method. A set of 60 questionnaires were distributed to the respondent and data was analyzed manually. All the data was analyzed and interpreted by using the SPSS statistical analysis software for windows application (version 19.0). From the findings, it was found that respondent understand the mission of outdoor education program to build and maintain a social condition, disciplined, knowledge and enhancing leadership skill.